2021
DOI: 10.48550/arxiv.2112.06938
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

J-PLUS: Uncovering a large population of extreme [OIII] emitters in the local Universe

Abstract: Context. Over the past decades, several studies have discovered a population of galaxies undergoing very strong star formation events, called extreme emission line galaxies (EELGs). Aims. In this work, we exploit the capabilities of the Javalambre Photometric Local Universe Survey (J-PLUS), a wide field multifilter survey, with 2000 square degrees of the northern sky already observed. We use it to identify EELGs at low redshift by their [OIII]5007 emission line. We intend to provide with a more complete, deep,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 97 publications
1
4
0
Order By: Relevance
“…Although strict comparisons with other samples are difficult due to the different imposed selection criteria, we find a fair agreement in the counts of our sample compared to the EELGs of Cardamone et al (2009), Yang et al (2017), andLumbreras-Calle et al (2021). Our counts are, however, slightly lower than those of Amorín et al (2015) who used the zCOSMOS data, but still within the uncertainties.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Although strict comparisons with other samples are difficult due to the different imposed selection criteria, we find a fair agreement in the counts of our sample compared to the EELGs of Cardamone et al (2009), Yang et al (2017), andLumbreras-Calle et al (2021). Our counts are, however, slightly lower than those of Amorín et al (2015) who used the zCOSMOS data, but still within the uncertainties.…”
Section: Discussionsupporting
confidence: 60%
“…In general, it is found that the rest-frame EW evolves with redshift as ionization efficiency increases (Sobral et al 2014;Khostovan et al 2016). Moreover, Lumbreras-Calle et al (2021) found a sample of EELGs at z ≤ 0.06 with [Oiii] EW over 300Å using 2000 deg 2 with the J-PLUS survey (Cenarro et al 2019).…”
Section: Introductionmentioning
confidence: 94%
“…A key detail for establishing a comprehensive and consistent framework relies on the assembly of a substantial number of exemplars across redshift. Predominantly through the exploration of deep narrow-or broadband photometry, several studies have contributed in this regard (e.g., Straughn et al 2009;van der Wel et al 2011;Amorín et al 2010;Atek et al 2011;Smit et al 2014;Lumbreras-Calle et al 2022). However, the information that can be extracted from this data type is rather limited, with the ideal being to acquire spectroscopic information for an equivalently high number of galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…And galaxies with large [O III] equivalent widths (EWs; from 200 Å to 800 Å) are widely used to address the Lyα continuum escape fraction in the high-z universe (Fletcher et al 2019;Katz et al 2020;Barrow et al 2020). Their analogs at low z refer to the so-called "Green Pea" galaxies (Cardamone et al 2009), showing strong [O III] emission with extremely high [O III]/[O II] ratio (Jaskot et al 2013;Yang et al 2017;Yuma et al 2019;Lumbreras-Calle et al 2021;Liu et al 2022). The [O III] lines redshift into the near-infrared (NIR) and middle-infrared (MIR) bands for z > 3 objects.…”
Section: Introductionmentioning
confidence: 99%